Transcranial Direct Current Stimulation in Children and Adolescents With Attention-Deficit/Hyperactivity Disorder (ADHD): A Pilot Study. (June 2016) - Bandeira, Igor Dórea; Guimarães, Rachel Silvany Quadros; Jagersbacher, João Gabriel; Barretto, Thiago Lima; de Jesus-Silva, Jéssica Regina; Santos, Samantha Nunes; Argollo, Nayara; Lucena, Rita
Studies investigating the possible benefits of transcranial direct current stimulation on left dorsolateral prefrontal cortex in children and adolescents with attention-deficit hyperactivity disorder (ADHD) have not been performed. This study assesses the effect of transcranial direct current stimulation in children and adolescents with ADHD on neuropsychological tests of visual attention, visual and verbal working memory, and inhibitory control. An auto-matched clinical trial was performed involving transcranial direct current stimulation in children and adolescents with ADHD, using SNAP-IV and subtests Vocabulary and Cubes of the Wechsler Intelligence Scale for Children III (WISC-III). Subjects were assessed before and after transcranial direct current stimulation sessions with the Digit Span subtest of the WISC-III, inhibitory control subtest of the NEPSY-II, Corsi cubes, and the Visual Attention Test (TAVIS-3). There were 9 individuals with ADHD according to Diagnostic and Statistical Manual of Mental Disorders (Fifth Edition) criteria. There was statistically significant difference in some aspects of TAVIS-3 tests and the inhibitory control subtest of NEPSY-II. Transcranial direct current stimulation can be related to a more efficient processing speed, improved detection of stimuli, and improved ability to switch between an ongoing activity and a new one.